IMPLEMENTASI BAHAN AJAR PADA MATA PELAJARAN PENDIDIKAN SENI RUPA MATERI DAUR ULANG KELAS IV MIS NU AL-UTSMANI KAJEN - Adi Prasetya, Uki; Sukmawati Putri, Adinda; Akhsanu Nadia, Irma; Najah, Syafinatun; Kamal, Rahmat (Ibriez : Jurnal Kependidikan Dasar Islam Berbasis Sains, 2024)
The issue of plastic waste has become a critical concern in modern development. One definite step in addressing this is through recycling. This research investigates the implementation of instructional materials based on recycling in the subject of Visual Arts for fourth-grade students at MIS NU Al-Utsmani Kajen. It connects the concept of recycling with the use of discarded items within the context of art education. A qualitative field method was employed using data triangulation through interviews, observations, and documentation to analyze the supporting factors and obstacles in using these instructional materials. The findings indicate that this approach is effective in educating students about the importance of environmental conservation through steps such as project determination, planning, execution, presentation, and teacher feedback. Supporting factors include comprehensive information in the instructional materials, evaluation of learning materials, and the use of a combination of textbooks and Student Worksheets (LKS). On the other hand, inhibiting factors include the tendency towards monotonous instructional materials and the lack of visual and interactive resources to enrich student learning experiences.